Peran Teknologi Pendidikan Dalam Meningkatkan Kualitas Pendidikan Di Era Disrupsi - Natalia Natalia; Taufik Muhtarom (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Along with the times, technology in its development certainly brings changes to life, especially in the world of education which will also continue to experience development. This article aims to determine the role of educational technology in improving the quality of education in this progressive era. So it is hoped that educational technologists will no longer feel doubtful and interested in adapting and being able to take advantage of technology with all its benefits in educational life. In writing this article we use a literature review method (library research), where researchers collect materials related to research from books, journals, scientific articles, literature and mass media coverage by describing and describing the data. Based on the discussion, it can be concluded that educational technology was created to solve learning problems by facilitating and providing alternatives and new innovations in the world of education. That way educational technology can make it easier to achieve educational goals.